Guided Discovery-based thermochemistry modules to enhance critical thinking ability and process science skills: development and experimental results - Obianto Babys, Jekson; Saputro, Sulistyo; Budi Utomo, Suryadi (International Journal of Educational Research & Social Sciences, 2024)
The purpose of this study was to determine the results of testing the development of chemical modules on thermochemical materials. The method used in this study is a mixed method, namely qualitative and quantitative methods. Twelve assertions about the module, including its substance, language, presentation, and graphics, were included in a questionnaire that was used to collect the data. In order to improve the module, respondents were given the opportunity to offer suggestions at the conclusion of the questionnaire. The research's trial portion was conducted in two stages, a minor test and a major test. Chemistry instructors and pupils from three state senior high schools served as the study's subjects. While 30 students and 5 teachers were present for the major trial, only 15 students and 3 teachers were present for the minor trial. The results of the quantitative analysis obtained an average minor test result of 73.91% in the good enough category for teachers and 74.72% for students in the good enough category. Major test results obtained an average of 82.5% in the very good category for teachers and 80.13% for students in the very good category. The qualitative method is based on the suggestions given by the teacher and students and obtained from the questionnaire. There were several suggestions for revisions obtained during these two stages, namely the need to add the amount of information about chemistry, add answers to questions in the module, add pictures or illustrations, correct some typing errors, and slightly enlarge the column of student answers in the module.